2005
DOI: 10.21273/hortsci.40.6.1821
|View full text |Cite
|
Sign up to set email alerts
|

Chlorophyll Fluorescence Imaging Allows Early Detection and Localization of Lemon Rind Injury following Hot Water Treatment

Abstract: Green lemons (Citrus limon (L.) Burm.) were imaged for chlorophyll fluorescence (CF) 30 minutes after immersion of the fruit into 55 °C water for 5 minutes to determine if CF could be used to identify areas of hot water-induced rind injury before the appearance of visible symptoms. Fluorescence was variable in intensity over the surface of the rind with defined areas of enhanced fluorescence being present that corresponded in shape and location with visible injury that later … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 22 publications
0
7
0
Order By: Relevance
“…CFI has also been used in lemons for the early detection of areas of hot water-induced rind injury before the appearance of visible symptoms during storage (Obenland and Neipp, 2005). Nonpathological rind disorders, which can be initiated in pre-and/or postharvest, are common occurrences that reduce the marketability value of the fruit (Grierson, 1981).…”
Section: Use Of Cfi During Postharvest Life Of Fruits and Flowersmentioning
confidence: 99%
See 1 more Smart Citation
“…CFI has also been used in lemons for the early detection of areas of hot water-induced rind injury before the appearance of visible symptoms during storage (Obenland and Neipp, 2005). Nonpathological rind disorders, which can be initiated in pre-and/or postharvest, are common occurrences that reduce the marketability value of the fruit (Grierson, 1981).…”
Section: Use Of Cfi During Postharvest Life Of Fruits and Flowersmentioning
confidence: 99%
“…F 0 and F m provided the best image contrast between injured and non-injured areas of the rind. The increase of F 0 observed in injured areas indicated photoinhibition damage (Obenland and Neipp, 2005). Nedbal et al (2000b) showed that CFI can be used in lemon to discriminate between damaged areas that, although visually similar, have different underlying causes.…”
Section: Use Of Cfi During Postharvest Life Of Fruits and Flowersmentioning
confidence: 99%
“…[10][11][12][13][14], and in phototrophic aquatic systems (e.g. [15][16][17], but this technique has been seldom used for photosynthetic measurements in fruits (18)(19)(20)(21)(22). Moreover, the few studies with imaging-PAM techniques have been directed to assess the ripening stage (23), fruit quality (18) or early injury detection (19) in intact fruits.…”
Section: Introductionmentioning
confidence: 99%
“…These induce visible fluorescence (550-500 nm) on molecules of essential oils present in the skin after cell breakage. Chlorophyll fluorescence was employed by Obenland and Neipp (2005) to locate incipient peel injury caused by hot water treatment in lemons. Visible-and UV-induced fluorescence (UVFL) was also used by Ariana et al (2006a) to detect different types of defects in three varieties of apples.…”
Section: Lightingmentioning
confidence: 99%